smurfy14
  • smurfy14
Can you check my answers? File attached (only 9 problems)
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
smurfy14
  • smurfy14
1 Attachment
anonymous
  • anonymous
checking now... 37 38 right
anonymous
  • anonymous
38 39 are right

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
first one is wrong
anonymous
  • anonymous
37 is not right lol
anonymous
  • anonymous
41 is wrong
anonymous
  • anonymous
fail... 3+2 = 5
anonymous
  • anonymous
^for 37
anonymous
  • anonymous
the last question is actually very easy
smurfy14
  • smurfy14
ok sorry i multiplied for some reason :P
smurfy14
  • smurfy14
41?
anonymous
  • anonymous
answer to 45 is just "3"
smurfy14
  • smurfy14
nvm i know how to do 41 and how did u get 3?
anonymous
  • anonymous
g(x) = -2f(x-1) + 5 , this given
anonymous
  • anonymous
now , g(3) , just means go the function and g , and everywhere you see an x , replace it with a 3
anonymous
  • anonymous
ie , g(3) = -2 f(3-1) + 5 // by subbing int the above
anonymous
  • anonymous
g(3) = -2f(2) + 5
anonymous
  • anonymous
but we were told f(2) = 1
anonymous
  • anonymous
the answer for 45 is 3
anonymous
  • anonymous
g(3) = -2 +5 = 3
smurfy14
  • smurfy14
ok i see thanks! so is everything else besades 41 correct?
anonymous
  • anonymous
lol I was too slow elecengineer (and I'm assuming that you're in electrical engineering.. which I am too haha)
anonymous
  • anonymous
no, 37 is wrong
smurfy14
  • smurfy14
well ya besides that?
anonymous
  • anonymous
37 should be +5
smurfy14
  • smurfy14
how do you do 42?
anonymous
  • anonymous
confirmed 44 righttttt
anonymous
  • anonymous
42 is inverse just switch the y and x around lemme see
anonymous
  • anonymous
so you have y=x+3 make it so that it is x=y+3
anonymous
  • anonymous
then you'll have y=x-3 where y=h^(-1)x
smurfy14
  • smurfy14
so whats the answer?
anonymous
  • anonymous
x-3
anonymous
  • anonymous
lol
smurfy14
  • smurfy14
oh ok and is the answer to 41 7x^3+36x^2+54x+28?
smurfy14
  • smurfy14
hello?
anonymous
  • anonymous
37. h(2+a) = (2+a)+3 = 5+a 38. correct 39. correct 40. correct\[41.f(x+h)-f(x) = [(x+h)^{3}+1]-(x ^{3}+1)\]\[=x ^{3}+h ^{3}+3x ^{2}h+3xh ^{2}+1-x ^{3}-1\]\[=h ^{3}+3x ^{2}h+3xh ^{2}\] \[42. h ^{-1}(x)=1/(x+3)\] \[43. f(x)*g(x) = (x ^{3}+1)(x ^{2}-2)\]\[=x ^{5}-2x ^{3}+x ^{2}-2\] 44. correct 45. g(x) = -2f(x-1)+5 g(3) = -2f(3-1)+5 = -2f(2)+5 = -2*1+5 f(2)=1 = -2+5 = 3

Looking for something else?

Not the answer you are looking for? Search for more explanations.